Bringing the Bottom Billion into Basic Literacy: How We Can and Why We Must. Issue 158 (15th December 2017) - Gottwald, Stephanie; Morris, Robin; Wolf, Maryanne; Galyean, Tinsley
Abstract: Close to one billion people in the world do not have basic literacy skills. A key challenge is reaching children in the midst of circumstances that make a traditional school‐based approach impractical. This chapter will describe a cross‐disciplinary, mobile technology approach to literacy education. The Curious Learning approach distributes research‐based, English literacy content on mobile devices to children without access to an adequate school. The software platform is equipped with data collection tools to measure usage patterns and literacy outcomes. Results indicate that regular access resulted in higher early literacy skills. Future efforts will focus on adapting this approach in the languages spoken in the homes of the children.